Adverse effects of incretin‐based therapies on major cardiovascular and arrhythmia events: meta‐analysis of randomized trials. Issue 8 (6th May 2016) - Wang, Tiansheng; Wang, Fei; Zhou, Junwen; Tang, Huilin; Giovenale, Sharon
Abstract: Background: Recent cardiovascular outcome trials of incretin‐based therapies (IBT) in type 2 diabetes have not demonstrated either benefit or harm in terms of major adverse cardiovascular events (MACE). Earlier meta‐analyses showed conflicting results but were limited in methodology. We aimed to perform an updated meta‐analysis of all available incretin therapies on the incidence of MACE plus arrhythmia and heart failure. Methods: We identified studies published through November 2014 by searching electronic databases and reference lists. We included RCTs in which the intervention group received incretin‐based therapies and the control group received placebo or standard treatment; enrolled> 100 participants in each group; interventions lasted> 24 weeks; and reported data on one or more primary major adverse cardiovascular events endpoints plus terms for arrhythmia and heart failure. We used the Peto method for each CV event for individual IBT treatment. Results: In this meta‐analysis of 100 RCTs involving 54, 758 incretin‐based therapies users and 48, 175 controls, exenatide was associated with increased risk of arrhythmia (OR 2.83; 95% CI, 1.06–7.57); saxagliptin was associated with an increased risk of heart failure (OR 1.23; 95% CI, 1.03–1.46), and sitagliptin was associated with a significantly decreased risk of all cause death compared to active controls (OR 0.39, 95% CI 0.18–0.82). Conclusions: In type 2 diabetes, exenatide may increase the risk of arrhythmia, and sitagliptin may reduce the risk of all cause death; however, the subgroup of patients most likely to experience harm or benefit is unclear. Copyright © 2016 John Wiley & Sons, Ltd.